Evaluation of Accounting Information System’s Implementation on Revenue Cycle - Fiqi Fazriana Firdauzi; Machmudin Eka Prasetya (International Journal of Economics Development Research (IJEDR), 2024)
Technology adaptation carried out by the Company needs to be accompanied by an adequate internal control process so that the objectives of implementing the technology can be met. Weaknesses in the identified system need to be assessed by analyzing the risks that need to be prioritized in the implementation of the accounting information system used, so that the Company can determine the mitigating response that should be carried out by the Company. The evaluation method in this research is qualitative in the form of a case study with a descriptive approach using the COSO ERM Framework. The research results state that the Company already has good capabilities in implementing the Company's internal controls. However, there were 13 risks identified in four departments related to the revenue cycle system. The mitigation response given was 12 reductions and one sharing. This research paper hopes that the Company can maximize the use of its IT team in the internal control process, so that it can create a system that meets the needs of both customers and employees.